Writing strategies among Nigerian student-writers - Bello, Mohammed; Harun, Minah (2018)
This article discusses Nigerian secondary school students’ strategies on writing narrative essays. More specifically, it examines written texts of fifteen second language learners of English in a public secondary school in adamawa state, Nigeria. Based on a purposive sampling strategy, the participants comprise male and female students between the age of fifteen and eighteen years old who can read and write in English language. Data collected were the narrative essays of the participants’ which were done in class. The written test took approximately forty-five minutes. The study reveals that the student-writers use three prominent strategies which include using cohesive elements in connecting ideas, using supporting details for clarity of information and discussing relevant points through the use of paragraph. The findings of this study direct attention to the importance of having knowledge of academic writing strategies among the school students’ to enable them to excel in an academic realm and the work place. Finally, the paper recommends that future research seeks to investigate the strategies used by Nigerian undergraduate or postgraduate students in written communication particularly, academic papers and dissertations.